AN INVESTIGATION INTO THE FLOUTING OF CONVERSATIONAL MAXIMS EMPLOYED BY MALE AND FEMALE GUESTS IN THE AMERICAN TALK SHOW “THE ELLEN SHOW” - Trần Thị Huyền Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This research is carried out with the aim of investigating pragmatic features of maxim flouting employed by male and female guests in the American talk show “The Ellen Show”. Besides, the study discovers similarities and differences in terms of conversational maxim flouting between two genders. The data for analysis are 72 situations of maxim flouting for each gender in “The Ellen Show”. In order to reach the goal, the study design was based on a combination of quantitative and qualitative approaches. The methods applied in the research were descriptive and comparative ones. The findings of this study reveal that although both genders shared some similarities in the pragmatic features of maxim flouting, each gender reflects its own tendency of language style in communication. With regard to types of maxim flouting, all four types proposed by Grice (i.e. Quality, Quantity, Relation and Manner) were identified in the samples of both genders. Additionally, instances of Mixed Maxim Flouting have been discovered in both genders. As far as rhetorical strategies are concerned, all six types of Grundy‟s rhetorical strategies consisting of Tautology, Metaphor, Overstatement, Understatement, Rhetorical Question and Irony were applied in conversational maxim flouting situations of male and female guests. However, there are a number of instances where no rhetorical strategies were used, especially the instances of female. Besides, Mixed Rhetorical Strategies have been discovered, but only in the instances of female guests. In terms of purposes of maxim flouting, 16 purposes employed by male and female guests were identified: joking, teasing the hearer, expressing one’s feeling, refusing a request, giving a clear explanation, saving face, showing modesty, showing politeness, emphasizing a fact, hiding the truth, maintaining self-esteem, maintaining relationship, satisfying the hearer, avoiding hurting the hearer, convincing someone and arousing curiosity. It is hoped that the results can contribute some useful knowledge to pragmatic features of maxim flouting in daily conversation as well as teaching and learning English to Vietnamese learners.